Management and Follow‐up Results of Salivary Fistulas Treated With Botulinum Toxin. (27th August 2018) - Send, Thorsten; Bertlich, Mattis; Eichhorn, Klaus W.; Bootz, Friedrich; Jakob, Mark
Abstract : Objectives/Hypothesis: Salivary fistulas are a common minor complication of parotid surgery. botulinum toxin has repeatedly been reported to be an adequate treatment of this entity. To date, there is little scientific evidence for clinical decision making after appearance of a salivary fistula. Study Design: Retrospective chart analysis of 16 patients who had been treated with botulinum toxin for salivary fistula. Methods: All patients who had been treated for salivary fistula at a tertiary referral hospital from 2010 to 2016 were included. Patient files were used to obtain characteristics of patients, treatment, and follow‐up. Results: Sixteen patients with salivary fistula received 27 injections of botulinum toxin. Nine patients required one injection for the fistula to heal, five patients needed two injections, and one patient needed three and four injections, respectively. No patient underwent additional surgery or radiotherapy. We observed no adverse effects in any patient treated with botulinum toxin. Conclusions: In most cases of salivary fistula, injections of botulinum toxin are a valid treatment. If the initial injection is not successful, injections may be repeated once. Otherwise, revision surgery should be considered. In general, treatment with botulinum toxin should be commenced in an earlier stage and with higher dosages. Level of Evidence: 4 Laryngoscope, 129:403–408, 2019